Psychological Characteristics of Future Teachers in Teaching Steam Technologies - Suvonova Lobar Islamovna (International Journal on Integrated Education, 2023)
Future specialists, today's graduate students should have pedagogical techniques to manage their self, their emotional state; being able to establish relationships with others; Since speaking is a process characterized by expressiveness of speech, mimicry, and pontamimic expressiveness, in article, we began to investigate the psychological characteristics of the development of pedagogical techniques in graduates. After all, according to the Law of the Republic of Uzbekistan "On Education", the use of modern science, technology, technology and cultural achievements is becoming important in order for the educational modules taught in higher education institutions to meet the requirements of the time.